Psycholinguistic markers of autobiographical and traumatic memory - Zasiekina, Larysa; Kennison, Shelia; Zasiekin, Serhii; Khvorost, Khrystyna; Засєкіна, Лариса; Кеннісон, Шіліа; Засєкін, Сергій; Хворост, Христина (Lesya Ukrainka Eastern European National University, 2019)
This study examines psycholinguistic structure of autobiographical and traumatic narratives representing positive emotional and stressful traumatic life events. The research applied the cross sectional, between subjects design utilizing the independent variables of external agent they, space and time and dependent variable of word number in traumatic narratives for multiple regression analysis. The approval letter to recruit the participants through SONA system in 2015– 2016 academic year was obtained from Institutional Review Board of Oklahoma State University (USA). 64 undergraduates of nonclinical setting, females (n=37), males (n=27), mean age was 19.43 (SD=1.37) were recruited. PTSD-8: A Short PTSD Inventory assesses PTSD, the Linguistic Inquiry and Word Count (LIWC) analyzes traumatic and autobiographical narratives in terms of linguistic units and psychological meaningful categories. The results indicate that there are significant differences between pronoun they as external agent of proposition and psychological categories of negative emotions and anxiety in traumatic and autobiographical narratives. The frequency of these categories is higher in traumatic narratives compared with autobiographical narratives. External agent they, category of time and space taken together significantly contribute to word number in traumatic narrative. There is a negative correlation between focus on the past and word count, and positive correlation between social category and word count in traumatic narrative in nonclinical sample. To sum up, propositional structure of traumatic memory of individuals without PTSD is represented by external agent and context (place and time) taken together. Considering time as a significant negative predictor of creating traumatic narrative, temporal processing without overestimation of time is an important factor of avoiding PTSD. The principal theoretical implication of this study is that traumatic memory might be examined through psycholinguistic markers represented by propositional structures and psychological meaningful categories of traumatic narratives in individuals from nonclinical and clinical settings.Мета дослідження полягала в теоретичному й емпіричному вивченні пропозиційної структури автобіографічної й травматичної пам’яті як сховища позитивних та травматичних життєвих подій. Дослідження використовує вивчення наративів незалежних вибірок із використанням регресійного аналізу, де категорії екстернального агента вони, часу і місця є залежними змінними, а кількість слів травматичного наративу – незалежною змінною. Дослідження здійснювалося за згодою Комісії з етики проведення психологічних досліджень Державного університету Оклахоми впродовж 2015–2016 навчального року. У дослідженні взяло учать 64 студенти, дівчат (n=37), хлопців (n=27), середній вік 19,43 (SD=1,37). Для емпіричного дослідження використовувався експрес-опитувальник ПТСР (PTSD-8: A Short PTSD Inventory), а також комп’ютерна програма Linguistic Inquiry and Word Count (LIWC) для визначення лінгвальних і психологічних категорій у тексті. У результаті, встановлено значущі відмінності у показниках категорій екстернального агента вони та психологічних категорій негативних емоцій та тривожності у травматичному та автобіографічному наративах. Травматичні наративи мають вищу частотність цих категорій, так само як і більшу кількість слів наративу загалом. Результати регресійного аналізу показують, що категорії екстернального агента, часу і місця є значущими предикторами кількості слів травматичного наративу, тому ми можемо вважати ці категорії як одиниці пропозиційної структури, і відповідно, психолінгвальні маркери травматичної пам’яті. Також встановлено негативний кореляційний зв’язок між кількістю слів у травматичному наративі і фокусом на минулому часові, та позитивний кореляційий зв’язок між соціальною категорією та кількістю слів у травматичному наративі. Отже, отримані результати можуть використовуватися для клінічних і неклінічних досліджень травматичної пам’яті на основі пропозиційних структур, представлених у травматичних наративах. Коректне темпоральне сприймання, уникання переоцінки минулого та переважання екстернальних над інтернальними агентами становлять пропозиційну структуру травматичної пам’яті індивіда, травматичний досвід якого не розвинувся у ПТСР.
Психолінгвальні маркери автобіографічної й травматичної пам’яті
Keywords: traumatic memory; autobiographical memory; PTSD; propositional structure; LIWC; травматична пам’ять; автобіографічна пам’ять; ПТСР; пропозиційна структура